Some Risk Factors for Low Birthweight Infants at Manado Hospital - S. M. Salendu W.; Sutomo Raharjo; Immanuel Mustadjab; Nan Warouw (Paediatrica Indonesiana, 1995)
The risk factors of low birthweight infants were assessed in a retrospective study covering 3607 singleton livebirth infants at Manado Hospital from January until December 1993. The analysis confirmed that patterns of risk birthweight hypertension in pregnancy (P<0.01), maternal education (P<0.01), maternal age (P<0.05), and parity (P<0.01), marital status (P<0.01), history of abortion (P<0.05), and parity (P<0.01). Anemia in pregnancy was also associated with birthweight in low birth weight (P<0.05). Asymetric intrauterine growth retardation (Ponderal Index below 2.32) was found both in premature and term infants.